ILLOCUTIONARY ACT OF GRUG UTTERANCES IN THE CROODS MOVIE - Lisnani, Lisnani; Arifin, M Bahri; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2017)
AbstractIllocutionary act is performing an act by saying something. There were five types of illocutionary act, namely: assertives, directives, commissives, expressives and declaratives. The Croods movie is a story about the journey of a family who wants to find a safer place for them to life. The aims of this research were to find out the types and to know the context of illocutionary act of Grug’s utterances in The Croods movie. This research was conducted by using descriptive qualitative method, because the data of this research were from the utterances containing the types and the context of illocutionary act of Grug’s utterances. The data of this research were taken from 38 sample utterances of Grug’s conversation. From the analysis can be concluded that they were 13 utterances in the form of assertive which can be categorized into stating, concluding and asserting. Thirteen directive utterances in the form of commanding, requesting, ordering, questioning and forbidding. Commissive appeared in six utterances in the form of promising and refusing. The last types of illocutionary act was expressive which appeared in six utterances in the form of thanking, apologizing, praising and stating anger. Key words: The Croods movie, illocutionary act, types, context AbstrakTindak ilokusi adalah melakukan suatu tindakan dengan mengatakan sesuatu. Ada lima jenis tindak ilokusi, yaitu: asertif, direktif, komisif, ekspresif dan deklaratif. Film The Croods adalah kisah tentang perjalanan sebuah keluarga yang ingin mencari tempat yang lebih aman bagi mereka untuk hidup. Tujuan dari penelitian ini adalah untuk mengetahui jenis dan untuk mengetahui konteks tindak ilokusi dari ucapan Grug di film The Croods. Penelitian ini dilakukan dengan menggunakan metode deskriptif kualitatif, karena data penelitian ini berasal dari ucapan-ucapan yang berisi jenis tindak ilokusi dan konteks tindak ilokusi dari ucapan Grug. Data penelitian ini diambil dari 38 sampel ujaran percakapan Grug. Dari hasil analisis dapat disimpulkan bahwa terdapat 13 ucapan dalam bentuk asertif yang dapat dikategorikan ke dalam menyatakan, menyimpulkan dan menegaskan. Tiga belas ucapan direktif dalam bentuk memerintah, meminta, pemesanan, mempertanyakan dan melarang. Komisif muncul dalam enam ucapan dalam bentuk menjanjikan dan menolak. Jenis terakhir dari tindakan ilokusi adalah ekspresif yang muncul dalam enam ucapan dalam bentuk berterima kasih, meminta maaf, memuji dan menyatakan kemarahan. Kata Kunci: film The Croods, tindak ilokusi, tipe, konteks